(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article examines the functional and methodological role of ethnotoponymy as a specialized branch of onomastics within the structure of general toponymy. The author analyzes ethnotoponyms as linguo-historical sources that allow reconstructing migration processes, determining the boundaries of ancient ethnic areas, and identifying substratum language layers. The study defines the key methods of ethnotoponymic analysis and, using the example of Karakalpakstan’s ethnotoponymy, proves its interdisciplinary significance for linguistics, history, and ethnography.